Differentiated squamous intraepithelial neoplasia associated with squamous cell carcinoma of the anal canal. Issue 6 (10th December 2015) - Wasserman, Jason K; Bateman, Justin; Mai, Kien T
Abstract : Aims: Differentiated squamous intraepithelial neoplasia (DSIN) has been described in several sites, including the upper aerodigestive tract and vulva, so this study investigated whether it also occurred in the anal canal. Methods and results: All cases of squamous cell carcinoma (SCC) involving the anal canal diagnosed between 2009 and 2015 at our institution were reviewed. Eighty‐six cases were included, and 13 (15%) showed features consistent with DSIN: 10 were 'pure' DSIN, and three were 'mixed' DSIN and squamous intraepithelial lesion. DSIN was characterized by atypical keratinocytes limited to the basal/parabasal layers, acanthosis, and a 'cobblestone' appearance. Among specimens with pure DSIN, the surface was flat in eight cases. In five cases, the DSIN was extensive, and associated with deeply invasive SCC requiring radical surgical resection. Immunohistochemically, the epithelia showing changes consistent with DSIN were p16‐negative, whereas the invasive component was p16‐positive in 12 cases. Both Ki67 and p53 showed strong nuclear positivity in the basal/parabasal layers of DSIN. Conclusions: Invasive SCC associated with DSIN often presents at an advanced stage of disease, requiring radical surgical treatment. The neoplastic changes in DSIN are limited to the basal/parabasal layers, which may account for the negative diagnoses by anal cytopathology and late clinical diagnosis. The recognition of anal DSIN is important in order to avoid underdiagnosis in superficial biopsies.